Incentives, project choice and dynamic multitasking - Martin Szydlowski (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2011)
I study the optimal choice of investment projects in a continuous time moral hazard model with multitasking. While in the first best, projects are invariably chosen by the net present value (NPV) criterion, moral hazard introduces a cutoff for project execution which depends on both a project's NPV as well as it's signal to noise ratio (SN). The cutoff shifts dynamically depending on the past history of shocks, current firm size and the agent's continuation value. When the ratio of continuation value to firm size is large, investment projects are chosen more efficiently, and project choice will depend more on the NPV and less on the signal to noise ratio. The optimal contract can be implemented with an equity stake, bonus payments, as well as a personal account. Interestingly, when the contract features equity only, the project selection rule resembles a hurdle rate criterion.
Keywords: D86; G11; G31; G32; M12; M52; 330; Continuous-time contracting; Project Choice; Multitasking; Bonus Payments; CEO Compensation